Trade and development: essays in economics - Ramaswami, V. K.; Bhagwati, Jagdish N.; Johnson, Harry G.; Srinivasan, T. N. (London : Allen and Unwin, 1971)
This book teaches the fundamental theory of international trade.
Includes bibliographies.
sju 22/01/2019
Loans
Keywords: Commerce; Economic development